Mechanical behavior of materials : engineering methods for deformation, fracture, and fatigue - Dowling, Norman E., 1945- (Upper Saddle River, NJ : Prentice Hall, 1999)
Comprehensive in scope and readable, this book explores the methods used by engineers to analyze and predict the mechanical behavior of materials. Author Norman E. Dowling provides thorough coverage of materials testing and practical methods for forecasting the strength and life of mechanical parts and structural members.
Mechanical Behavior of Materials also features reviews of materials science and stress and strain. This Second Edition includes updated coverage throughout, additions to the already numerous worked examples, and two new appendices.
1. Introduction -- 2. Structure and Deformation in Materials -- 3. A Survey of Engineering Materials -- 4. Mechanical Testing: Tension Test and Other Basic Tests -- 5. Stress-Strain Relationships and Behavior -- 6. Review of Complex and Principal States of Stress and Strain -- 7. Yielding and Fracture under Combined Stresses -- 8. Fracture of Cracked Members -- 9. Fatigue of Materials: Introduction and Stress-Based Approach -- 10. Stress-Based Approach to Fatigue: Notched Members -- 11. Fatigue Crack Growth -- 12. Plastic Deformation Behavior and Models for Materials -- 13. Stress-Strain Analysis of Plastically Deforming Members -- 14. Strain-Based Approach to Fatigue -- 15. Time-Dependent Behavior: Creep and Damping -- App. A. Review of Selected Topics from Mechanics of Materials -- App. B. Statistical Variation in Materials Properties.
Includes bibliographical references (p. 807-818) and index.
Keywords: Mechanical enginering -- ME